Membangun Generasi Peduli Lingkungan Dalam Kegiatan Kuliah Kerja Nyata Di Korong Lapau Jambu Nagari Sungai Durian - Afdal Zikri; Joni Indra Wandi; Nurva Dillatul Vatin; Fatwah Nur Azizah; Nurihsan Nurihsan; Riza Febriyani; Ririn Anisa Agustin; Zakky Novembri (Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) in Korong Lapau Jambu, Nagari Sungai Durian, aims to foster an environmentally conscious generation through various community service initiatives. In this program, university students collaborate with local communities to address environmental issues such as waste management, reforestation, and education on the importance of environmental conservation. The methods used include socialization, training, and hands-on actions involving all community members, especially the younger generation. The results of this activity showed an increase in environmental awareness among the community, particularly the youth, which is expected to have a long-term impact on environmental sustainability in Nagari Sungai Durian. This program also emphasizes the importance of active participation from all parties in protecting nature and building environmental awareness from an early age.